2016
DOI: 10.3928/01477447-20160719-03
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Diaphyseal Femur Fractures: Submuscular Plating Compared With Intramedullary Nailing

Abstract: This study compared the radiographic and clinical outcomes of pediatric diaphyseal femur fractures treated by submuscular plating, flexible retrograde intramedullary nailing, or rigid antegrade intramedullary nailing with a trochanteric entry point in skeletally immature patients who were 8 years and older. A retrospective review was conducted of skeletally immature patients 8 years and older who were treated for femur fracture with submuscular plating, flexible intramedullary nailing, or rigid intramedullary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
47
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 30 publications
3
47
0
1
Order By: Relevance
“… 20 A study published in 2016 compared postoperative outcomes in 198 skeletally immature patients eight years or older who underwent treatment with SMPs, FNs or rigid intramedullary nailing, and did not examine surgical parameters such as EBL or operative time. 21 Our study results are consistent with those of the 2012 study in terms of operative time and EBL 20 and with the 2016 study in terms of a higher incidence of irritation among patients treated with FNs (23% of 61 patients treated with FNs versus 2.9% of 35 patients treated with SMPs, p not reported). 21 Soft-tissue irritation has been reported as a complication of FNs in multiple studies, with incidence ranging from < 10% to as high as 52% 22 but is minor in most cases and relieved with implant removal.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“… 20 A study published in 2016 compared postoperative outcomes in 198 skeletally immature patients eight years or older who underwent treatment with SMPs, FNs or rigid intramedullary nailing, and did not examine surgical parameters such as EBL or operative time. 21 Our study results are consistent with those of the 2012 study in terms of operative time and EBL 20 and with the 2016 study in terms of a higher incidence of irritation among patients treated with FNs (23% of 61 patients treated with FNs versus 2.9% of 35 patients treated with SMPs, p not reported). 21 Soft-tissue irritation has been reported as a complication of FNs in multiple studies, with incidence ranging from < 10% to as high as 52% 22 but is minor in most cases and relieved with implant removal.…”
Section: Discussionsupporting
confidence: 92%
“… 21 Our study results are consistent with those of the 2012 study in terms of operative time and EBL 20 and with the 2016 study in terms of a higher incidence of irritation among patients treated with FNs (23% of 61 patients treated with FNs versus 2.9% of 35 patients treated with SMPs, p not reported). 21 Soft-tissue irritation has been reported as a complication of FNs in multiple studies, with incidence ranging from < 10% to as high as 52% 22 but is minor in most cases and relieved with implant removal. 8 , 21 , 23 – 25 Proposed risk factors for irritation include bent or prominent nail ends, 22 earlier mobilization of the knee 12 and excessive nail protrusion at the time of implantation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The treatment of choice for pediatric femur fractures remains dictated by the child's characteristics, the fracture pattern, and the treating surgeon's preferences. While locked compression plate fixation has shown at least twice the stiffness and increased torsional stability when compared with titanium elastic nails, flexible nailing has the advantages of minimal soft tissue dissection, faster operative times, and decreased surgical costs, with equivalent outcomes when used in the appropriate patients [14][15][16]. Plating is accompanied by the potential risks of delayed healing from soft tissue stripping, femoral over-children may diminish the need for restricted weight bearing, similar to the protocol employed for locked intramedullary nailing.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study conducted by Sean et al, comparing 3 modalities management of fracture shaft of femur found out that, a significant association was found between treatment type and fracture pattern A higher proportion of spiral fractures and fewer transverse fractures were found in the plate group. 8 The mean time of fracture union radiologically was statistically insignificant, were mean time of union in group A it was 12 weeks were as in Group B it was 13.1 weeks. Study conducted by Kumar et al observed the mean union in TENS group in femur fracture was 13.00±1.37 and another studies observed that union rate in children's managed with DCP to fracture shaft of femur was between 8-11 weeks.…”
Section: Discussionmentioning
confidence: 99%